Fabrication of carbon materials by direct ink writing of hydrogel precursors - Milani, Christy (2019)
Porous carbon materials manifest excellent chemical stability, large surface area and are utilized in wide range of applications, but fabrication of structured carbon are often limited by the soft, free-flowing nature of the carbon powders. 3D printing offers unequalled flexibility to attain intricate geometries and high mechanical performance which are unachievable by conventional manufacturing techniques. The aim is to produce high performance and cheap structural carbon products without requiring expensive custom casting and post machining operations. In this project, a carbon precursor hydrogel blend was synthesized by reacting carbon precursors with a thermoplastic PVA matrix. Subsequently, the blended material underwent extrusion process via a 3D printing machine. This machine utilises a direct ink writing technique to fabricate complex and simple 3D structures. Moreover, sodium tetraborate was added to transform the precursor hydrogel into a flubber-like substance to aid in structure retention of the printed product. Three carbon precursors were compared and dicyandiamide was found to display better processability and carbonization product, against phthalonitrile and melamine. Characterisation techniques such as TGA, FTIR, SEM and DSC were performed to analyse the physical and chemical properties of the end products obtained from the three precursors. The experiments concluded that dicyandiamide had the ideal solubility and thermal stability.